IMPROVEMENT OF DISSOLUTION RATE OF VALSARTAN BY SOLID DISPERSION SYSTEM USING D(−) MANNITOL - Zaini, Erizal; Umar, Salman; FIRDAUS, NURHIDAYAH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: To improve dissolution rate of valsartan from solid dispersion system of valsartan and D(−) mannitol using co-grinding approach. Methods: Valsartan solid dispersion with different ratio of D(−) mannitol (1:1; 1:3 and 1: 5) were prepared by co-grinding method. Solid state characterization of the solid dispersion system was evaluated in term of crystallographic properties (powder X-ray diffraction), thermal behavior (differential scanning calorimetry [DSC]) and morphology (scanning electron microscope). The profile of dissolution rate was examined using USP dissolution apparatus type I at a temperature of 37±0.5°C. Results: Based on thermal analysis DSC and powder X-ray diffraction analysis, valsartan was transformed from semicrystalline phase to amorphous state as indicated by the disappearance of its melting endothermic peaks and the characteristic diffraction peaks. The in vitro dissolution rate study revealed that all solid dispersion system showed significant increase in dissolution rate compared with the intact valsartan. Conclusion: Solid dispersion of valsartan with D(−) mannitol prepared by co-grinding technique has successfully improved the dissolution rate compared with intact valsartan. Keywords: Valsartan, D(−) mannitol, Solid dispersion, Co-grinding, Dissolution rate.